Professional socialization of hospital nurses: A scale development and validation study - Seongmi Moon; Soo Jung Chang (BMC, 2023)
Abstract Background Tools currently available to measure professional socialization are outdated or could not reflect various properties of professional socialization of nurses. Thus, the objective of this study was to develop and validate a professional socialization measurement instrument for hospital nurses. Methods Fifty-two items were initially extracted from literature reviews and in-depth interviews with 32 nurses. After content validity testing, 48 items remained. They were used to survey 881 hospital nurses in Korea in the testing phase for construct validity and reliability. Results: Four factors (21 items) were extracted: ethical practice and reflection, perception of respect and recognition, clinical competency based on leadership, and desires and motivation for professional development. These factors demonstrated good construct validity and reliability. Correlation coefficients of professional socialization with professional value, compassion satisfaction, secondary traumatic stress, and burden were 0.58 (p < 0.001), 0.70 (p < 0.001), − 0.08 (p = 0.014), and − 0.56 (p < 0.001), respectively. Reliability had a Cronbach's alpha of 0.95. Test-retest reliability intraclass correlation coefficient was 0.90. Conclusions The four professional socialization scale factors in this study reflected attributes of knowledge, skills, values, and professional roles. Professional socialization of nurses can be continuously developed by emphasizing elements of the professional socialization scale in nursing education programs. Nursing managers should help nurses go through the professional socialization process. The professional socialization scale will serve as a tool for developing careers of hospital nurses.